Deep Excavation Retaining Systems In Unsaturated Soils - Tariq B. Hamid (Deep Foundations Institute, 2006)
Deep excavation is commonly associated with construction of different deep below-grade structural elements (e.g., basement walls and slabs, tunnels, retaining walls, tanks, utilities, etc.) Deep Excavation Retaining Systems (DERS) are required when open cuts with safe slopes are not possible. Careful analysis, design, and planning of the DERS are required to provide safe below-grade construction and secure nearby structures from damaging effects that may result from the deep excavation. Selection and design of temporary or permanent DERS (e.g., soldier pile and lagging, sheet piling walls, secant pile walls, tie backs, etc.) can have significant impact on time, cost, and performance. In order to design DERS using conventional methods, it is necessary to obtain shear strength parameters, angle of internal friction (ø), and cohesion (c), of retained soils. Residual shear strength parameters (ø'res, c'res) obtained from drained direct shear tests and triaxial tests on saturated samples have been commonly used in practice for the analysis and design of DERS. However, there are cases where ground water table remains at or below the base of excavation during the design lifetime of DERS. In such cases, the soil above the ground water table is in an unsaturated state. Therefore, it is important to account for the unsaturated conditions of soils in order to optimize the design of DERS. This paper is focused on implementing the basic concepts of unsaturated soils mechanics including matric suction and soils-water characteristic curve (SWCC) to estimate design shear strength parameters of unsaturated soils (i.e., ø°, c', and ø') for the design of a cantilever sheet pile walls, a typical case of study of the DERS. The results of this study indicate that the determination of unsaturated soil strength shear strength parameters is simple. In addition, using unsaturated soil mechanics theories has an outstanding impact on the design of retaining systems.